Adaptive Renewal of Mountainous Historical Towns Based on the Stability of the Social Network Structure: A Case Study in Chongqing, China - Yaling Shi; Yong Huang; Yong Huang; Ran Zhang; Di Jiang; Junxue Zhang (Frontiers Media S.A., 2022)
The stability of social network structure (SSNS) in historical towns is influenced by changes in built environments and demographic factors. The historical towns in China have evolved into massive rural-urban migration under the rapid urbanization over the past forty years. In this context, many of these historical towns experienced "declining built environment and disintegrating social networks," which does not contribute to the adaptive renewal of the built environment and social networks in historical towns, as well as the psychological health of residents. This article intends to explore the adaptive renewal of the built environment and social networks of historical towns based on the SSNS. Data on "households" and "social ties" (i.e., kinship, geographic, and job relationship) among households were collected via a field survey in seven historical towns in Chongqing, China. K-core models of social network analysis (SNA) were calculated to analyze SSNS. The result shows that the social networks of historical towns with centripetal-shaped structures were more stable than historical towns with divergent-shaped structures. Moreover, spatial layout forms and functions of households might affect the stability of social networks in historical towns. Based on the results of the analysis of SSNS, strategies for adaptive renewal of the built environments and social networks were put forward in two aspects. The built environment, such as the classification of public spaces and service facilities, can be designed based on the k-core indicator for increasing the spatial connection of households in the historical towns. In addition, increased social activities in historical towns with weak SSNS may promote social connection of households, and are also helpful in boosting public health in psychological aspects.